2011
DOI: 10.1097/smj.0b013e3182142ba0
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal Endocarditis

Abstract: Fungal infections of the heart are increasingly described especially in immunocompromised patients. Cardiac involvement can present with myocarditis, pericarditis or endocarditis. Cryptococcal endocarditis is extremely rare, with only four reported cases in the literature. The prognosis, natural history and the optimal management for cryptococcal endocarditis are not well described because of paucity of cases. We report the case of a patient with prosthetic aortic valve endocarditis due to C. neoformans. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…There have only been seven previously reported cases of Cryptococcal endocarditis in the literature. These cases are summarized in (Table 1) [15][16][17][18][19][20][21]. The earliest case was reported in 1957 and the most recent was published in 2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have only been seven previously reported cases of Cryptococcal endocarditis in the literature. These cases are summarized in (Table 1) [15][16][17][18][19][20][21]. The earliest case was reported in 1957 and the most recent was published in 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, culture-negative endocarditis accounts for 35% of cases [13,14]. Cryptococcus represents an extremely rare pathogen in endocarditis with only seven reported cases [15][16][17][18][19][20][21]. Little is known regarding the natural history and optimal management given the limited available data.…”
Section: Introductionmentioning
confidence: 99%
“…FE typically occurs in otherwise critically ill patients and is often part of a confusing clinical picture, with most patients having difficulty meeting the Duke criteria for IE [ 25 ] . Transthoracic echocardiography is less sensitive than transesophageal echocardiography (TEE), but is also less invasive.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptococcal endocarditis is extremely rare and has been reported in post-operative prosthetic valve infections [ [24] , [25] , [26] , [27] , [28] , [29] ]. Lombardo et al reported the first case of Cryptococcus endocarditis in 1957 [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to paucity of reported cases, no randomized trials(RCT) have been done to give clinicians a guideline based on RCTs to follow or to compare Amphotericin-B therapy with surgical management. Alhaji et al in 2011 reported a case of prosthetic valve endocarditis successfully treated with Amphotericin-B [ 28 ]. Colmers et al in 1967 reported success with medical therapy as well [ 26 ].…”
Section: Discussionmentioning
confidence: 99%